2015
DOI: 10.1590/1679-78251486
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Performance of Cable-sliding Modular Expansion Joints Subject to Near-fault Ground Motion

Abstract: According to the research fruits of the diverse damages of bridge in the past, bearings' invalidation is the main reason of the damage of isolated bridges and causes oversized relative displacements between pier and girder. Eventually, it may lead to severe collision of superstructure. It is extremely dangerous when near-fault motion occurs, because it has obvious velocity pulse effect and increases the risk of colliding between girders.Aiming at this problem, this paper puts forward a device named cable-slidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 13 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…Numerous researches have been conducted to control the pulse effects of near-fault ground motions on base isolated bridges. Gao et al (2015) proposed a cablesliding modular expansion joint which significantly decreased the relative peak displacement due to near-fault ground motions. Ghosh et al (2012) studied the types of seismic isolators in the response of continuously curved bridges in plan under the influence of the near-fault ground motion of Kobe and found that LRB, HDRB and FPB systems could reduce the response of pier displacement and force.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researches have been conducted to control the pulse effects of near-fault ground motions on base isolated bridges. Gao et al (2015) proposed a cablesliding modular expansion joint which significantly decreased the relative peak displacement due to near-fault ground motions. Ghosh et al (2012) studied the types of seismic isolators in the response of continuously curved bridges in plan under the influence of the near-fault ground motion of Kobe and found that LRB, HDRB and FPB systems could reduce the response of pier displacement and force.…”
Section: Introductionmentioning
confidence: 99%